Traumatic hemipelvectomy (amputae): Report of one case (Medical Journal of Indonesia, 2001)
Traumatic hemipelvectomy (amputae) is a catastrophic injury resulting front violent shearing forces which avulsed the lower limb at the level sacroiliac joint and symphisis pubis. Patients surviving traumatic hemipelvectomy are rare. One case of a 25 months old girl surviving traumatic hemipelvectomy), is presented. This is the first case reported from Indonesia. (Med J Indones 2001; 10: 169-73)